Antimicrobial resistance in the environment - Keen, Patricia L.; Montforts, M. H. M. M. (Wiley-Blackwell, 2012)
"This book explores the role that environmental distribution of antimicrobial resistance genes and antibiotics plays in ecosystem and human health. The text features a multi-disciplinary framework that connects microbiology, environmental toxicology, and chemistry to assess human and ecological risk associated with exposure to antibiotics or antibiotic resistance genes as environmental contaminants. It also considers alternate uses and functions for antimicrobial compounds other than those intended for medicinal purposes in humans, animals, and fish. Recognizing the connectivity between overlapping complex systems, the book discusses the subject from the perspective of an ecosystem approach"--